Empowerment of peer group in prevention of drug abuse - Camellia, Vita; Siregar, Mastauli (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Hutauruk Village in Sipoholon Subdistrict is one of the tourist destination locations in North Tapanuli, which is a hot spring which is very crowded with tourists from outside Taput. with a very high rate of drug abuse. Due to the large number of outsiders coming this allows the rampant drug abuse that occurred in the village of Hutauruk due to the influence of outside culture that entered the village. Drug abuse is carried out by teenagers, adults and parents. In this village there are many groups of teenagers who use drugs. In the mechanism of substance abuse, peer groups (peer groups) have an influence that can encourage or trigger drug abuse in a person. Peers have an influence on the consumption behavior of substances such as tobacco, alcohol, and other drugs. Peer is an external factor that can also influence adolescence, both positive and negative promiscuity. This service was carried out in Hutauruk Village, Sipoholon District, North Tapanuli Regency. The output target of this service is partners understanding the importance of healthy living without drugs, being able to build self-confidence, being able to manage a doormeer business, building a doormeer business that fills in leisure time and a new source of income for partners because it brings economic value.